Hepatitis C virus infection in Australian psychiatric inpatients: A multicenter study of seroprevalence, risk factors and treatment experience. Issue 5 (16th January 2019) - Ramachandran, Jeyamani; Budd, Silver; Slattery, Hannah; Muller, Kate; Mohan, Titus; Cowain, Taryn; Tilley, Emma; Baas, Andrea; Wigg, Laura; Alexander, Jacob; Woodman, Richard; Kaambwa, Billingsley; et al.
Summary: Screening and treatment for hepatitis C virus (HCV) infection were not prioritised in psychiatric patients due to adverse neuropsychiatric effects of interferon therapy despite reports of high prevalence. However, with the safe new antiviral drugs, HCV eradication has become a reality in these patients. The aim of this study was to report HCV seroprevalence, risk factors and treatment model in an Australian cohort. This prospective study involved patients admitted to four inpatient psychiatric units, from December 2016 to December 2017. After pretest counselling and consent, HCV testing was done; information on risk factors collected. A total of 260 patients (70% male), median age 44 years (IQR 24), were studied. The HCV seroprevalence was 10.8% (28/260) with 95% CI 7‐15. Independent predictors of HCV positivity were injection drug use ( P  < 0.001, OR 44.05, 95% CI 7.9‐245.5), exposure to custodial stay ( P  = 0.011, OR 7.34, 95% CI 1.6‐33.9) and age ( P  = 0.011, OR 1.09, 95% CI 1.02‐1.16). Eight of the 16 HCV RNA‐positive patients were treated. Hepatitis nurses liaised with community mental health teams for treatment initiation and follow‐up under supervision of hepatologists. Seven patients achieved sustained viral response, one achieved end of treatment response. The remaining eight patients were difficult to engage with. In conclusion, HCV prevalence was high in our cohort of psychiatric inpatients. Although treatment uptake was achieved only in 50% patients, it was successfully completed in all, with innovative models of care. These findings highlight the need to integrate HCV screening with treatment linkage in psychiatry practice.